PENGARUH PENAMBAHAN EKSTRAK DAUN SALAM TERHADAP UMUR SIMPAN BAKSO - Tantri Yulianti; Dewi Cakrawati (Agroindustrial Technology, University of Trunojoyo Madura, 2017)
Meatball was Indonesian favorite food made from meat, seasoning and additives. Meatball was perishable due to high water content and nutrition therefore to increase it shelf life there was a need to add natural preservative that have the ability to prevent the growth of microorganism. The aims of the research was to determine the effect of addition on bay leaves extract to the meatball characteristics. The research was conducted using experimental method. The independent variable was bay leave concentration, consist of four stages there were 1%, 2% and 3%. Dependent variables consist of organoleptic characteristics, microorganism using Total Plate Count method, were measure each 2 days during 6 days storage. Result showed addition of bay leave extract can extend meatball shelf life in room temperature for two days. After two days, meatball was deteriorated shown by high number of microorganisms, off-flavor, soft texture